Portrayal of Women's Emancipation in Enola Holmes 2: A Feminist Literary Analysis - Hanifa, Lulu Fadlina; Hakim, Arief Rahman; Djohar, Hasnul Insani (NOBEL: Journal of Literature and Language Teaching, 2025)
This study explores the representation of women’s emancipation in Enola Holmes 2 through the lens of feminist literary criticism. Using Mansour Fakih’s theory of emancipation, the research examines how the film portrays women’s struggles and resistance in three key areas: economy, education, and politics. The film centers on Enola Holmes, a young female detective navigating systemic gender discrimination in Victorian England. Through her challenges in establishing a career, her involvement in the Matchgirls Strike of 1888, and the mentorship she receives from her mother, the film demonstrates the multidimensional nature of emancipation. Enola’s journey symbolizes both personal empowerment and collective resistance, aligning with both liberal and socialist feminist perspectives. Her development as an independent, capable figure, along with the solidarity shown among female characters like Sarah Chapman and Mira Troy, reflects ongoing struggles against patriarchal norms. This study highlights how cinema can function as a powerful medium to critique historical and contemporary gender inequalities. The film does not only entertain but also educates and inspires audiences to reflect on women’s continuous efforts toward freedom, agency, and equality. By reconstructing historical narratives with a feminist lens, Enola Holmes 2 contributes significantly to popular feminist discourse.